Experimental study on the bearing capacity and effective anchorage lengths of inclined steel grouting pipes in loess embankment slope. - Jiawei Fan; Yufang Zhang; Kun Yuan; Wenjiao Zhou (PLoS ONE)
Splitting grouting is widely used to reinforce unfavorable soil stratum. Inclined steel grouting pipe is a type of structure which can achieve splitting grouting in soil stratum. It has been successfully utilized in argillaceous sandstone stratum, but its application in loess stratum has rarely been studied directly. This research aims to compare and analyze the bearing capacity and effective anchorage lengths of inclined steel grouting pipes with anchorage lengths of 6 m, 9 m, and 12 m. Firstly, bearing capacity of inclined steel grouting pipe was compared with that of ordinary grouting pipe. Secondly, bearing capacity of inclined steel grouting pipe with anchorage lengths of 6 m, 9 m, and 12 m were compared and analyzed. Thirdly, effective anchorage lengths of inclined steel grouting pipe with anchorage lengths of 6 m, 9 m, and 12 m were compared and analyzed. Finally, inclined steel grouting pipe average cohesive strength along effective anchorage length section at the interface between cement grouting and soil stratum was compared with that of rock bolt. The field experimental results illustrated that: (1) The bearing capacity of inclined steel grouting pipe with anchorage length of 9 m increases 22.6% compared with that of ordinary grouting pipe. (2) Anchorage length is not a significant influence factor for bearing capacity of inclined steel grouting pipes in loess embankment slope, while anchorage length is a significant influence factor for modulus of load-displacement curves of inclined steel grouting pipes in loess embankment slope. (3) Effective anchorage length of inclined steel grouting pipe in loess embankment slope will be slightly increased when increasing anchorage length, while the ratio of effective anchorage length to total anchorage length will be decreased when increasing anchorage length. (4) Inclined steel grouting pipe average cohesive strength along effective anchorage length section at the interface between cement grouting and soil stratum is at least three times compared with that of rock bolt.